Determinan Kemampuan Auditor dalam Mendeteksi Kecurangan - Suryanto, Rudy; Indriyani, Yosita; Sofyani, Hafiez (Journal of Accounting and Investment, 2017)
This study aims to examine the influence of experience, workload, profesional skepticism, and personality type NT (Intution-thinking) toward the ability to detect fraud of auditors. The intensive search using the Rasch model approach developed by George Rasch with the involvement of auditors working in Yogyakarta and Surakarta as the study sample. This study fiund that the auditor's experience and personality type affect the auditor's ability to detect fraud. While the workload and profesional skpetisme auditor assessed not affect the auditor's ability to detect fraud. More detailed results of this study are presented in this paper.